"Wholly Useless and Unserviceable to Knowledge": Locke's Practical Case Against Species Realism - Wörner, David (Locke Studies)

(untitled) (Western Libraries at The University of Western Ontario, 2023)
In this paper I examine Locke’s criticism of the view that some species of natural objects are determined by real essences, a view I call species realism. Most commentators have focused either on Locke’s putative objections to the realist’s claim that species determining real essences exist or on his semantic case against the assumption that our species terms can refer to real essences that determine species. I identify another objection, which, I argue, is independent from both of these lines of criticism. This objection is essentially practical. It is based on the claim that adopting species realism has detrimental practical consequences: it undermines, Locke believes, our ability to sort particular natural objects into species. This alone, he argues, is already sufficient to set aside and ignore species realism when trying to sort objects into species.